Web-Based Inpatient Reporting System at AFIFA Clinic: Sistem Pelaporan Pasien Rawat Inap Berbasis Web di Klinik AFIFA - Akrom, Mohammad Faizinal; Nisak, Umi Khoirun (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Efficient medical record management is essential for quality healthcare services. Specific Background: At AFIFA inpatient and maternity clinics, reporting is still conducted manually through registers, leading to inefficiency and errors. Knowledge Gap: Few local clinics have implemented structured web-based inpatient reporting systems despite national policies on electronic medical records. Aims: This study aimed to design and implement a web-based inpatient reporting application to improve reporting accuracy and efficiency. Results: Using interviews, direct observations, and the Rapid Application Development (RAD) method, a web-based system was developed with modules for patient registration, diagnosis, inpatient monitoring, and reporting. The system minimized errors, reduced reporting time, and provided more accurate outputs compared with manual processes. Novelty: Unlike traditional reporting, the application integrates multiple reporting processes into a single system accessible in real-time. Implications: The system facilitates efficient clinical reporting, supports regulatory compliance, and can be adopted by similar healthcare facilities. Highlight: Web-based reporting reduces errors and delays in clinical data. RAD method enables fast and reliable system development. Supports compliance with electronic medical record standards. Keywords: Web-Based System, Inpatient Reporting, Medical Records, RAD Method, Health Information